‘The existing state of affairs is a disgrace and a positive danger to the town’: Water-borne disease and sanitation in the Beaufort West Municipality, 1848-1955 (Historia, 2024)
For more than two centuries, Beaufort West has been an essential stopover for people traversing an arid and sparsely populated region. Throughout its existence, the town has been plagued by water problems, whether they be drought, flash floods, or sanitary in origin. Many factors contributed to Beaufort West’s sanitary woes. Situated in the semi-arid central Great Karoo with an average rainfall of a mere 250mm, Beaufort West’s unique geographical positioning renders it climatologically vulnerable and because its water supply is heavily reliant on rainfall, regular droughts are inevitable. Groundwater extracted from boreholes has played an increasingly important role in the development of Beaufort West. Since the 1850s, it has been reliant on a very rudimentary potable water reticulation system of open street furrows, and a sewage system comprising cesspools and pail removals. Until the first half of the twentieth century many of the residents were self-sustaining and on their properties they kept farm animals such as pigs, sheep, goats, fowl and cows as food and horses as draught animals. These conditions created almost unsurmountable sanitation problems. The council minutes and sanitation reports of the Beaufort West Municipality frequently note the prevalence of two diseases – typhoid and diphtheria. This article investigates the root causes, manifestation, and health impact of these diseases on the community of Beaufort West. It traces the municipal initiatives to combat their occurrence, and the efforts made to improve the town’s general sanitary conditions. This case study of Beaufort West corroborates a hypothesis that modern-day outbreaks of water-borne diseases and sanitation in South Africa have a long historical antecedent.